Relationship of Caffeinated Beverage Intake with Sleep Quality of 2020 Students' Faculty of Medicine Tarumanagara University - Wendy Tan; Meilani Kumala (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Sleep is a condition in which a person becomes less aware of something. Short rest periods (<7 hours) can increase the risk of death and have been considered a major risk factor for damaging the endocrine system, immune system, nervous system, and cardiovascular system. Many factors affect sleep duration and sleep quality in adults and children, including the use of caffeinated beverages. The purpose of this study was to determine whether there was a relationship between the intake of caffeinated beverages and the sleep quality of the 2020 students of the Faculty of Medicine, Tarumanagara University. The research is a descriptive-analytic cross-sectional study. Data was collected by distributing g-form to respondents. The collected data were inputted and analyzed using SPSS with Chi-Square and Fisher's Exact as an alternative analysis for cells with an expected of less than five. The results of this study showed that 41.3% of respondents had good sleep quality, and 58.7% of respondents had poor sleep quality. There is a significant relationship between coffee intake and sleep quality (p-value = 0.044), and there is no significant relationship between intake of tea, chocolate drinks, soft drinks, and energy drinks with sleep quality. The value of the prevalence ratio of caffeinated beverages intake with sleep quality is greater than one, which indicates caffeinated beverages are a risk for poor sleep quality.